People are conditional rule followers - Pieter Desmet; Christoph Engel (Max Planck Institute for Research on Collective Goods, 2017)
Experimental participants are more likely to follow an arbitrary rule the more of their peers do so as well. The difference between unconditional and conditional rule following is most pronounced for individuals who follow few rules unconditionally.
Keywords: A13; C91; D03; D63; K42; 330; conditional rule following; deontological motives; conditional cooperation; experiment